Pelaksanaan Putusan Pengadilan Militer In Absentia Terhadap Anggota TNI Yang Disersi - Agus Prambowo Sulistiyo; Joko Sriwidodo; Hedwig A. Mau (Qiyas : Jurnal Hukum Islam dan Peradilan, 2023)
Abstract : The definition of trial in absentia is to try without the presence of the defendant in the trial. In Indonesian law, courts in absentia can be applied to cases of road traffic violations, economic crimes, subversion and corruption.In the judicial process in absentia by the military court against suspects whose members of the military are absent or fleeing, those concerned can be processed using Law Number 39 of 1947, Article 86 and Article 87 concerning Amendments to the Army Criminal Code.The purpose of this study is to analyze, explain the implementation of the decision of the military court in absentia against members of the military who deserted and to analyze, explain the arrangements for the implementation of the decision of the military court in absentia against members of the military who deserted.This research is included in normative juridical research. The normative juridical research method is a method or method used in legal research which is carried out by examining existing library materials. The data used is secondary data. While the collection of legal materials is done by reviewing and collecting library materials and the analysis method is carried out by qualitative descriptive methods.From the results of the study, it can be concluded that based on the Decision that the Researcher reviewed, namely Decision Number 125-K/PM.II-09/AD/VIII/2021 and Decision Number 87-K/PM I-03/AD/IX/2021 it can be seen that the Implementation of the Military Court Decision this cannot be implemented. Because the defendant did not know his whereabouts Keywords : TNI members, in absentia, Desertion.